FACTORS INFLUENCING USER PERCEPTIONS OF QRIS IN THE DIGITAL PAYMENT ECOSYSTEM - Libran Filani; Lusiana Desy Ariswati (Program Studi Ekonomi Pembangunan, 2026)
This study examines the factors influencing the perceived usefulness of the Quick Response Code Indonesian Standard (QRIS) among Generation Z in the supporting regions of the Nusantara Capital City (IKN), namely Samarinda, Balikpapan, Kutai Kartanegara, and Penajam Paser Utara. Using the Technology Acceptance Model (TAM), this research analyzes the effects of social influence, perceived ease of use, trust, digital experience, and service innovation on perceived usefulness. A quantitative approach was employed, collecting data from 250 respondents aged 18-25 years through an online questionnaire distributed via Google Forms. Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis was used to test the relationships between variables. The results indicate that perceived ease of use and service innovation significantly influence perceived usefulness, explaining 82.7% of its variance, while social influence, trust, and digital experience have no significant effects. These findings emphasize that user-friendly interfaces and innovative features are crucial for enhancing QRIS adoption in developing regions. This study contributes to the theoretical application of TAM in non-metropolitan contexts and offers practical recommendations for improving QRIS adoption through digital infrastructure enhancements and service innovations.